FINANCIAL STABILITY OF HOUSEHOLDS AND TERRITORIAL COMMUNITIES UNDER INSTABILITY CONDITIONS: ELASTICITY TO THE ECONOMIC PROGRESS - MULSKA, Olha (Scientific journal «World of Finance», 2023)
Introduction. Household finances are an existential element of the financial system, the basis of its stability and the driver of economic growth of the territory. The financial stability of households and communities has a causal connection with the socio-economic progress of regions and the country, contributes to the development of the domestic consumer market, increasing the competitiveness of the territory, increasing the resource provision of economic reproduction and revival. The purpose of the article is to establish the degree of sensitivity and impact of the financial stability of households and communities on the economic growth of regions in conditions of socio-economic instability. Results. A methodical approach to assessing the impact of the financial sustainability of households and communities on the economic growth of regions has been developed, complementary testing of which makes it possible to establish the degree of elasticity of economic growth to changes in the financial stability of households and communities in different run-lags, as well as to accept the financial and investment potential of the region to ensure the economic sustainability of households in conditions of socio-economic uncertainty. It is proved that the financial stability of households has a positive impact on the economic development of regions (2019–2021). The economic growth of the regions is determined by the financial stability of households and communities in the range of 1.5–2.4 % and 1.9–2.6 %, respectively. It is determined that the financial stability of households and regional economic progress has a differentiated temporal-causal relationship (in the short-run, the reverse impact of the financial stability of households on economic growth can be traced). A high degree of elasticity was detected economic growth from the volume of tax revenues, the level of budgetary autonomy and financial self-sufficiency of communities as determinants of their financial stability. Conclusions. The financial stability of households has a causal relationship with determinants of macroeconomic development; investment and financial potential of households determines the development of the domestic consumer market, aggregate demand in the economy of the region, economic progress of the territory in general. The perspective of further scientific research is evaluation sensitivities of the financial stability of households to macroeconomic ones shocks. Prospects. The subject of further research is to assess the degree of sensitivity of the financial stability of households to macroeconomic shocks.